Discourse Analysis of Racism in Just Mercy Movie: Racism - Muhammad Nazar; La Aso; Ela Martisa (ELITE: Journal of English Language and Literature, 2024)
This research aims to describe the racism utterances in the Just Mercy movie using racism theory based on Dijk's approach. Researcher used qualitative descriptive research as a method. The data source in this research was taken from the Just Mercy movie. Data collection was carried out through watching, Note-Taking, Screen shooting, Identifying and grouping the data based on the theory of racism based on Dijk's approach. Data analysis techniques are presenting the data, describing the data, interpreting and analyzing the data resulting from this research. The research results show that racist behavior in the Just Mercy movie is depicted based on Dijk's theory in the aspects of nonverbal structures, sounds, syntax, lexicon, local (sentence) meaning, global discourse meaning (topics), schema (conventional forms of global discourse organization), rhetorical devices, speech acts, and interaction. This aspect shows racist actions in the form of facial expressions, voice, speech, actions and use of language styles. Racism in this research then provides an accurate picture of racist behavior towards black people as a reflection of the existing system of prejudice and stereotypes. As a results of the analysis, the researcher found that the movie had elements of racism in which Bryan Stevenson became a victim of racism. The researchers found seven data. Therefore, racial discrimination can also be seen in language discourse. Language also plays an important role in forming and maintaining the ideology of racism.